Pengaruh Return On Asset Dan Ukuran Perusahaan Terhadap Manajemen Pajak - Jesica Heriani Manullang; Zulia Hanum (Politeknik Ganesha Medan, 2022)
This study aims to determine the effect of return on assets (ROA) and company size on tax management in the automotive sub-sector companies and their components listed on the Indonesia Stock Exchange. This research is a of associative research. The sampling technique was carried out using a purposive sampling technique. So the sample is 11 automotive sub-sector companies and their components listed on the Indonesia Stock Exchange in 2015 - 2020 with a total of 66 observational data for 6 years of observation. The data collection technique used is with data sources using secondary data the official website of the Indonesia Stock Exchange. The data analysis technique used in this study is multiple linear regression analysis with SPSS 26 software. The results of this study indicate that return on assets (ROA) has no significant effect on tax management. Firm size has a significant effect on tax management. Return on assets (ROA) and firm size have no significant effect on tax management simultaneously.